Conhecimento tático declarativo de jogadores de futebol profissional e amador - Alves, Daniel Medeiros (2010)
This study aimed to compare the level of tactical knowledge declarative (CTD) of football players and amateurs alike, and describe factors that may contribute to the development of CTD. The sample consisted of 32 subjects divided into 2 groups: the GP was formed by 16 professional soccer players with a mean age of 29.63 (SD = 5.46) years and GA was formed by 16 amateur soccer players, without experience in professional football, with a mean age of 24.28 (SD = 4.87) years. We analyzed two variables: the CTD, by testing the Bag (1999) and the factors that contributed to developing the CTD through a questionnaire. We used SPSS 12. The test results of CTD were compared using the Wilcoxon test for unpaired samples and the results of the questionnaire was used descriptive statistics showing the frequency and percentage that were cited factors relevant to the acquisition of the CTD. The results showed that the levels of CTD of professional athletes had to be superior in relation to amateur athletes (p = 0.006). The reasons for this difference may be related to the factors mentioned in the study as relevant to the acquisition of the CTD. The main findings were "Tactical Training", "Experience in Competition" and "Image Base", "Technical Training" and "games and playing in the streets," suggesting that these factors have great contribution to the development of players as respect to decision-making demonstrated in test CTD.